The Effect of Training Quality, Work Environment, and Gender Equality Policy on Loyalty of Female Workers in Ethnic Tourism in Yogyakarta - Wahdiniawati, Siti Annisa; Sono, Moh Gifari; Haryadi, Haryadi (West Science Interdisciplinary Studies, 2024)
This study investigates the effects of Training Quality, Work Environment, and Gender Equality Policy on the loyalty of female workers in the ethnic tourism sector of Yogyakarta, Indonesia. Utilizing a quantitative approach, data were collected from 150 female employees through structured questionnaires, and analyzed using Structural Equation Modeling (SEM). The results reveal significant positive relationships between all three independent variables and employee loyalty. Training Quality exhibited the strongest influence (β = 0.663, p < 0.001), followed by Gender Equality Policy (β = 0.470, p < 0.001) and Work Environment (β = 0.335, p < 0.01). The findings underscore the importance of investing in effective training programs, fostering a supportive work environment, and implementing robust gender equality policies to enhance employee loyalty. This research contributes to the understanding of workforce dynamics in the tourism sector and offers practical implications for managers seeking to improve retention and performance.